2018
DOI: 10.1038/s41467-018-04542-9
|View full text |Cite
|
Sign up to set email alerts
|

Quantum limit transport and destruction of the Weyl nodes in TaAs

Abstract: Weyl fermions are a recently discovered ingredient for correlated states of electronic matter. A key difficulty has been that real materials also contain non-Weyl quasiparticles, and disentangling the experimental signatures has proven challenging. Here we use magnetic fields up to 95 T to drive the Weyl semimetal TaAs far into its quantum limit, where only the purely chiral 0th Landau levels of the Weyl fermions are occupied. We find the electrical resistivity to be nearly independent of magnetic field up to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
87
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 97 publications
(104 citation statements)
references
References 54 publications
16
87
1
Order By: Relevance
“…1(b)]. This threshold scale agrees qualitatively with the observed field strength above which the anomalous conductivity disappears in TaAs [7]. A parallel analysis can be applied to the remaining eight pairs of W2 nodes that share a similar node structure, but are off the k z = 0 plane.…”
Section: Gapping Of Chiral Lls In Weyl Semimetalssupporting
confidence: 73%
See 4 more Smart Citations
“…1(b)]. This threshold scale agrees qualitatively with the observed field strength above which the anomalous conductivity disappears in TaAs [7]. A parallel analysis can be applied to the remaining eight pairs of W2 nodes that share a similar node structure, but are off the k z = 0 plane.…”
Section: Gapping Of Chiral Lls In Weyl Semimetalssupporting
confidence: 73%
“…Surprisingly, it was found that the anticipated negative longitudinal magnetoresistance started to break down at large magnetic field (B ∼ 50 T), implying a gap opening and the loss of chiral anomaly. A second surprise is that the exponential rise in resistivity saturates at low temperature and the saturated resistivity decreases at even higher field strength (B ∼ 80 T) [7]. Gap opening has also been suggested in other Weyl materials such as TaP [8] and previous numerical studies also support similar ideas [9,10].…”
Section: Introductionmentioning
confidence: 76%
See 3 more Smart Citations